Improving indoor environmental quality (IEQ) for occupant health and well-being: A case study of Swedish office building. Issue 3 (November 2020) - Jin, Quan; Wallbaum, Holger
Abstract: Indoor environmental quality (IEQ) is a major domain of building conditions relating to occupant comfort, health and well-being. Especially in the office environment, IEQ can influence work productivity positively. Within the 17 UN Sustainable Development Goals (SDGs), goal 3 good health and well-being, and goal 8 decent work and economic growth are the two areas where IEQ can significantly contribute. To better design sustainable office buildings in line with the agenda 2030, the study aims to examine occupant satisfaction, health and work in a newly renovated office building which is labelled by the BREEAM certification scheme Silver. Occupant preferences of IEQ comparing to the current conditions were also explored to provide advice for future design. The results show that occupant satisfaction with IEQ has not well achieved and in the office environment occupants prefer warmer temperature, more fresh air, less noise, and more daylight. We also find that perceived IEQ is extensively related to occupant health and work productivity. It concludes that in such a newly renovated office building as a high-performance building, there are still many problems from the indoor environments. Therefore, improvements are needed to gain occupant satisfaction and positively influence occupant health, well-being and work productivity.